Job Satisfaction as a Mediating Variable in the Influence of Intellectual Capital Dimensions on the Performance of Village Officials - Panjaitan, Lusiani Nur; Trihudiyatmanto, M. (Jurnal Akuntansi, Manajemen dan Perbankan Syariah, 2024)
This research aims to analyze the Effect of Intellectual Capital (Human Capital, Social Capital, and Structural Capital) on the Performance of Village Apparatus and Performance of the Village Consultative Organization in Indonesian: Badan Permusyawaratan Desa (BPD) through Job Satisfaction as a Mediation Variable (Case Study on BPD and Village Government in Karangsari Pejawaran Banjarnegara Village). This research used a quantitative approach. The sample used was 135 respondents who were people from Karangsari Pejawaran Banjarnegara Village and questionnaires as a tool for collecting respondent data. The analytical method used in this research uses partial lest square (PLS) with outer inner model coefficient test. Based on the results of Based on the results of this study, it show that Human Capital and Structural Capital have a positive and significant effect on the performance of village apparatus and BPD. Social Capital does not significantly affect the performance of village apparatus and BPD. Human Capital, Social Capital and Structural Capital have a positive and significant effect on Job Satisfaction. Job Satisfaction is unable to mediate the influence of Human Capital, Social Capital and Structural Capital on the performance of village apparatus and BPD.